POSSIBILITIES OF INCREASING THE EFFICIENCY OF TEACHING MODERN PHYSICS IN HIGHER SCHOOL - Eshtuxtarova, Orzigul; Urazov, Abdixoliq; Umirov, Homid (Физико-технологического образование, 2021)
The article deals with the problems of teaching selected issues of modern physics in universities. The problems arising in the presentation of theoretical questions are analyzed, the possibilities that open up in connection with the development of sensor systems are shown: the use of standard sensor systems for solving various experimental problems; the use of modeling physical objects on a PC, replacing complex special equipment; the possibility of transferring some of the experimental tasks to home conditions; use of data obtained with the help of remote experimental equipment.